BREAKING DIGITAL BARRIERS: THE ROLE OF FINANCIAL LITERACY IN ACCELERATING INCLUSIVE FINANCING FOR SMEs - Nindy Puspitasari; Nurul Septya Magisa; Nur Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of financial literacy on digital adoption by examining the mediating roles of perceived digital barriers and business characteristics in Small and Medium Enterprises (SMEs). Data were collected through a survey using structured questionnaires and analyzed using Structural Equation Modeling (SEM) with WarpPLS 8.0. The findings reveal that financial literacy has a positive and significant effect on perceived digital barriers, business characteristics, and digital adoption. Furthermore, perceived digital barriers and business characteristics significantly influence digital adoption. The R-square value of 0.672 indicates that financial literacy, perceived digital barriers, and business characteristics collectively explain 67.2% of the variance in digital adoption. These results highlight that financial literacy not only strengthens business management practices but also fosters critical awareness of technological barriers, thereby enabling SMEs to be better prepared to embrace digital adoption and access inclusive financial services.